The Application of Think Pair Share Learning Model to Increase Student Activity and Learning Outcomes - Cicik Juhairiyah; Sholahudin Al Ayubi; Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
This research aims to improve student activity and learning outcomes through the application of the Think Pair Share learning model. This type of research is classroom action research (CAR). The subjects of this research were students of class VII MTs. Nurul Islam Ranuyoso. The data collection methods used was test, observation, interview and documentation methods. This research was conducted in two cycles, namely cycle I and cycle II. Based on the results of the research conducted, it was obtained data related to student activity in the first cycle of 63% and the second cycle of 87%. Then for the completeness of student learning outcomes before the research was 36.6%, in the first cycle it was 54.5%, and in the second cycle it was 82%. Based on the results obtained, it can be concluded that the application of the Think Pair Share learning model can increase student activity and learning outcomes. Keywords: think pair share, activity, learning outcomes